PENGARUH PENGETAHUAN LINGKUNGAN TERHADAP NIAT BELI PENDINGIN RUANGAN PLASMACLUSTER DENGAN SIKAP PADA LINGKUNGAN SEBAGAI PEMEDIASI - Agustini, Ni Kadek Ayu; Artha Kusuma, Anak Agung Gede Agung (E-Jurnal Manajemen; Vol 5 No 3 (2016), 2016)
Testing purposes in this study to test the role of attitudes on the environment in mediating the effects of environmental knowledge on purchase intention Sharp Plasmacluster air conditioning in Denpasar. Non-Probability Sampling methods used in the determination of the selected sample 110 respondents, with data collection via questionnaires 5-point Likert scale to measure 11 indicators. Path analysis is used to analyze the role of attitudes on the environment in mediating the effects of environmental knowledge on purchase intention Sharp Plasmacluster air conditioning in Denpasar. The influence of positive and significant environmental knowledge both to the environment and attitude on purchase intention Sharp Plasmacluster air conditioning in Denpasar. Attitude positive and significant impact on purchase intentions Sharp Plasmacluster air conditioning in Denpasar. The study also proved that the attitude of environmental knowledge significantly mediates the effects of the environment on purchase intention Sharp Plasmacluster air conditioning in Denpasar.
Keywords: Pengetahuan Lingkungan, Sikap Pada Lingkungan, Niat Beli